Demokrasi lokal di era kenormalan baru: peran media baru dalam pilkada serentak 2020 (Jurnal Kajian Media, 2023)
The simultaneous local elections in 2020 gave its own color to the implementation of local democracy in Indonesia. The ongoing pandemic situation has forced election organizers to adjust the implementation of the local election to the "New Normal" policy issued by the government. As a result, many local election activities that have been carried out physically have to switch to online media. Although, there are many pros and cons related to its implementation, especially because of the pandemic, the local election continued to run successfully. One of the reasons is because the new media have become an integral part in holding the simultaneous local election. This study will focus on the role of new media, especially social media, in the implementation of the simultaneous local elections in 2020. The data ware obtained through a literature review process, involving textbooks, scientific journals, and online mass media coverage. The results showed that new media, especially social media, played a very important role in the implementation of the local election. The presence of new media has prevented the implementation of democracy from being hampered due to the pandemic, but instead has found other areas where people can still engage in politics.